School Examination Stress Precipitating Hematohidrosis in a Girl - Anupama Vikram; J Christy Maria Viagulum; Poovazhagi Varadarajan (Wolters Kluwer Medknow Publications, 2023)
Background: Hematohidrosis is a rare clinical disorder characterized by transient, self-limited bleeding from the eccrine sweat glands through intact skin in the absence of an underlying bleeding disorder. Clinical Description: We report a 10-year-old girl who presented with a history of bleeding from the dorsum of her right hand. The child has had recurrent episodes in the past. Many of the episodes were temporally related to her school examination. She did not have any other bleeding manifestations or susceptibility to bruising. Her general condition and systemic examination were unremarkable, and the skin underlying the bleeding site was normal and healthy. All investigations related to bleeding and coagulation parameters were within normal limits. Skin biopsy showed normal histology. Having ruled out all organic causes of bleeding, the typical history of transient episodes of bloody secretions from the skin, triggered by examination stress and normal skin histology, was consistent with a diagnosis of hematohidrosis. Management: The child responded dramatically to oral propranolol with a subsequent reduction in the frequency of the bloody sweating episodes, even during stressful times. Psychological counseling was also provided. Conclusion: In a child presenting with oozing of blood from the skin, a possibility of hematohidrosis may be considered, when all causes of bleeding diathesis have been ruled out by a thorough workup. Pediatricians need to counsel both parents and the child regarding the benign nature of the condition.